Stakeholder dynamics of contextual ambidextrous capabilities and authenticity: A conceptual synchronisation for competitive advantage - Shams, S. M. Riad; Vrontis, Demetris; Thrassou, Alkis; Themistocleous, Christos; Christofi, Michael (My University, 2020)
The combined effect of strategic ambidextrous management (dynamic capabilities and contextual ambidexterity), marketing and brand communication management has been implicitly and explicitly identified as bearing critical implications for competitive advantage. However, the mutual influence of these knowledge streams on competitive advantage as well as its key component of contextual ambidexterity are much under-researched. This article follows an inductive constructivist method to develop a theoretically founded conceptualisation of the means through which the various stakeholder contextual ambidextrous dynamic capabilities can leverage the organisational authenticity learning process in cross-functional management to explore and exploit new competitive advantage scopes. Specifically, this research proposes a theoretically synchronised conceptual framework that focuses on identified key attributes of the knowledge streams, interlinking their individual and combined influences on brand positioning and corporate reputation for the creation of competitive advantage. Scholarly and empirical implications are also presented along with future research avenues.
Keywords: Authenticity; Brand positioning; Competitive advantage; Contextual ambidexterity; Dynamic capabilities; Organisational learning; Reputation; Resource-based view; Stakeholders